The Analytical Interpretation of Classical Alice in Wonderland in the Movie Adaptations of Walt Disney (1951) and Tim Burton (2010) Through a Feminist Perspective and Symbolism - Burcin Hasanoglu (European Scientific Journal, ESJ, 2023)
Alice’s Adventures in Wonderland is a world-wide known, fictional, British children’s book with its fantastical tales and riddles by Lewis Carroll. Being translated into more than 174 languages, it has also been the source of inspiration for some famous studios like Walt Disney and movie directors like Tim Burton. In Walt Disney’s adaptation (1951), the audience witnesses an Alice who is a courteous and curious child having a vast and vivid world of imagination with her neat and clean, blue-white dress. The characterization of Alice is very much similar to the book in terms of reflecting the time in which the book was written. Alice is a smart girl who is both educated according to the fashion of her time and different with her creativeness when it comes to dreaming of a “wonderland” that is full of nonsense when compared to the tedious mindset of the society in which she lives. On the other hand, Alice in Wonderland (2010) is transformed into a real masterpiece by the 21st century-movie director Tim Burton. He remains loyal to the characters; however, he presents a young, energetic Alice with a great imagination as usual. She is bolder, more independent, stronger both in mind and soul, and more feminist. In the movie, while she is considered to be mature enough to get married according to the norms and customs of 19th century England, she ends up as a dragon slaying heroine in underland. So, this paper aims to analyse how classical Alice in Wonderland is interpreted in the movie adaptations by Walt Disney (1951) and Tim Burton (2010) through a feminist perspective and symbolism.